A qualitative comparative study: Coping strategies among food secure and insecure pregnant mothers during the COVID-19 pandemic in Serang District - Gloriana Seran; Dwi Nastiti Iswarawanti; Diana Sunardi (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
The COVID-19 pandemic exacerbated the food security dimension, from the macro to micro level. Households dealt with the crisis by implementing coping strategies led by mothers. Consequently, these impacted their health and nutrition status, notably during pregnancy. This unfavorable condition was due to their primary role in maintaining household food security. This study aimed to explore the perceptions of pregnant mothers of food security and insecurity about their household coping strategies. This study used phenomenology with purposive sampling, with 33 informants (21 pregnant mothers and 12 other informants) in Serang district from May to October 2022. In-depth interviews (IDIs) were used during data collection, and the transcripts were verbatim. Respectively, the data was analyzed using thematic coding with N-Vivo 12 Plus and Microsoft Excel. Result, twenty-one pregnant mothers from food-secure (n=7) and insecure (n=14) households revealed adopting the food-focused coping strategies: rationing, scratching, seeking, and sharing. Non-focused on food: sought new job and side hustle, sold assets, borrowed money. Differentiation was the barter which the food insecure family solely adopted. Conclusion, both food-secure and insecure households implemented 2 types of coping strategies, while the severe coping strategies were implemented by food insecure pregnant mothers.